Estimation of rain erosivity in the city of Piaçabuçu – AL (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Soil erosion is the process caused by an erosive agent, which acts under the soil, precipitation, being the reason for the water erosive process, where detachment and transport by the surface runoff of soil particles occurs, this phenomenon depends on the intensity, frequency and duration of events in a given region. The municipality of Piaçabuçu is located in the region of the lower São Francisco Alagoano, therefore, the objective was to determine the rainfall erosivity indexes through the pluviometric data for the municipality of Piaçabuçu - AL, in the period from 1943 to 1985. These data were tables for calculating rain, the rain coefficient and its relation to erosivity using six equations. The municipality of Piaçabuçu has an average annual rainfall of 1128.52 mm, for the observation period of 42 years, with a wide variation in the distribution of rainfall over the years, with the rainy season concentrated in the months of April to August , presenting average values ​​above the average, in this period more than 70% of the rainfall precipitated for the municipality. All six models of erosivity estimates showed a correlation considered high, which enables them to estimate the erosivity of the municipality under study.